LABORATE TEST FOR FE LEVELS IN KELAKAI BISCUITS - Febby Siharina; Fitri Yuliana; Agustinus Hermino S. Putra (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2020)
As one of the causes of anemia, iron deficiency must be overcome immediately, one of which is by finding taste-friendly food sources that can be consumed easily by anyone who is prone to anemia. This research was conducted in laboratory to determine the levels of iron in Kelakai biscuits which are assumed to be a source of food to treat anemia in adolescent girls or pregnant women. Qualitative and quantitative test were used to obtain the desired results. Based on the research results, it was found that each Kelakai biscuit contained an Fe level of 245 mg/g, which means that the formulation of the Kelakai biscuit could meet the daily needs of iron when consumed 3-4 chips per day based on the absorption of Fe in adults. Therefore, to further prove the effectiveness of these biscuits in preventing anemia, studies involving samples, either small or large scale, are highly recommended.